Iron salts and vitamins: use, purchase and sources of obtainment among children in Brazil - Juliana do Amaral Carneiro Diel; Andréa Dâmaso Bertoldi; Tatiane da Silva Dal Pizzol (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
To verify the prevalence of use, purchase and sources of iron salts and vitamins by children aged from 0 to 12 years in Brazil. Population-based transversal study (Brazilian National Survey on Access, Utilization, and Promotion of Rational Use of Medicines - PNAUM), including 7,528 children up to 12 years of age. Information was obtained through questionnaires answered by the children's tutors, about the use of iron salts and vitamins 15 days before the interview; forms of financing, and sources of obtainment, sociodemographic characteristics, and presence of chronic disease. Descriptive and bivariate analyses were performed and the main variables were expressed by relative frequencies and 95% confidence intervals (95%CI). The prevalence of use of iron salts was 1.6% (95%CI: 1.2-2.1), with higher prevalence among children under 1 year old (8.5%; 95%CI: 6.3-11.5) and residents of the southeastern region (2.3%; 95%CI: 1.5-3.4). Prevalence of use of vitamins was 4.8% (95%CI: 4.2-5.6), with higher prevalence among children under 1 year old (24.3%; 95%CI: 20.3-28.7) and residents of the northern region (8.6%; 95%CI: 6.2-11.7). Purchase occurred by direct reimbursement for 41.6% (95%CI: 27.9-56.7) of the iron salts, and for 82.4% (95%CI: 76.3-87.2) of the vitamins. The iron salts were predominantly obtained from SUS pharmacies (51.5%; 95%CI: 36.4-66.4), and the vitamins from commercial pharmacies (80.6%; 95%CI: 77.4-85.6). The results suggested the use of iron salts in the Brazilian pediatric population was low, with reduction in use as age increased, regional differences and free-of-charge obtainment, predominantly from SUS.